Sistem Informasi Penjualan Pada Apotek Karunia - Supatra, Antoni; Ziveria, Mira (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2017)
Apotek Karunia is one of the companies engaged in the field of medicines whose business processes are still using a manual way that consists of the process of ordering goods, the process of making notes and invoices, the process of sending back and the process of selling drugs to the customer. Such a system still takes a long time to perform data processing so that the time required is not efficient. Therefore, to overcome these obstacles required a sales information system. This study aims to build a sales information system on a pharmacy gift using prototype development method. System analysis using flowchart, system design using unified modeling language (UML) modeling, system development or coding using Dot Net programming language and database using SQL Server, and system testing using black box testing. The result of the research is a sales information system used to process drug data, drug sales, and customer data collection.